1998
DOI: 10.1159/000018582
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of the Hydatid Disease of the Liver into the Biliary Tracts

Abstract: Background: To analyze the diagnosis and the surgical treatment of intrabiliary ruptured hydatid disease of the liver. Methods: Between 1990 and 1995, 263 patients with hydatid cysts of the liver underwent surgery in a university hospital. Twenty-five (9.43%) patients with intrabiliary rupture of hepatic hydatid cyst were retrospectively reviewed. Results: Diagnosis was principally made using ultrasonography and computed tomography scanning and was confirmed by the findings of other tests. In 12 patients (48%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 20 publications
0
39
1
4
Order By: Relevance
“…Obstructive jaundice and/or cholangitis are sensitive indicators of the presence of a frank CBF in more than 60% of the cases (7,11,20,21 If the bile ducts are evaluated with pre-operative ERCP, it is not necessary to do common bile duct exploration (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obstructive jaundice and/or cholangitis are sensitive indicators of the presence of a frank CBF in more than 60% of the cases (7,11,20,21 If the bile ducts are evaluated with pre-operative ERCP, it is not necessary to do common bile duct exploration (22).…”
Section: Discussionmentioning
confidence: 99%
“…Frank or major fistula is a wide communication between the cyst and the biliary system that allows the contents of the cyst to drain into the biliary system causing obstructive jaundice, cholangitis, secondary infection of the cyst, or even anaphylaxis (11).…”
Section: Introductionmentioning
confidence: 99%
“…The only other case report of spontaneous hepatic cyst regression was a congenital cyst in a 6-week-old infant [19]. The remaining literature that discusses the disappearance of cysts, typically hydatid cysts, attributes resolution to either fistula formation into the biliary or enteral tracts or intraperitoneal rupture [20,21]. Our patient had no evidence of rupture or fistula.…”
Section: Discussionmentioning
confidence: 74%
“…In most cases, US yields a diagnosis of the parasitic pathology and the presence of complications, but CT and MR may be required to confirm clinicaleechographic suspicions [19,20]. In cases of rupture of the cyst into the bile ducts, US can also reveal indirect signs of complications, such as dilation of the bile ducts and communication of the cyst with a bilio-vascular branch, as well as direct signs characterized by the presence of echogenic material without acoustic shadow in the common bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…Until a few years ago, treatment of complications in echinococcosis, like that of hydatid disease, was largely surgical [15,20,21], but some recent studies have demonstrated that endoscopic papillotomy is a valid procedure in the rupture of human cystic echinococcosis into the bile passages. It provides a certain diagnosis, shown by hydatid membranes exiting the common bile duct, while the opening of the papilla allows elimination of the membranes and protoscolices and resolution of the biliary obstruction, thus allowing medical treatment of the cyst (Albendazole).…”
Section: Discussionmentioning
confidence: 99%